Saree cancer in Indian woman treated successfully with multimodality management - Unmesh Vidyadhar Takalkar; Shilpa Balaji Asegaonkar; Pushpa Kodlikeri; Ujwala Kulkarni; Virendrakumar Borundiya; Suresh H. Advani (PAGEPress Publications, 2014)
Saree is a common, traditional garment of Indian women, wrapped around the waist tightened by a thick cord and with one end draped over the shoulder. Tight knot in the same place, sweat, soiling and continuous use can cause pigmentation, scaling of the waist and even transform to malignancy. We present here a case of saree cancer successfully managed with multimodality therapy. A 50-year-old woman was referred to our hospital (India) for itching and non-healing ulcerative lesion on waistline. She was wearing saree continuously for 34 years with knot at the same place. Magnetic resonance images suggested ulcerative growth with lymph node metastasis. She then underwent wide local excision; histopathological examination confirmed it was a squamous cell carcinoma. She therefore received concomitant chemotherapy and radiotherapy. She is now (2 years after the completion of treatment) in remission state. Awareness of saree cancer among Indian is important to avoid malignant lesions at waistline. Multimodality management with surgery, chemotherapy and radiotherapy is ideal mean for good outcome.